The Relationship between Clinical Guidance and Student Satisfaction During Clinical Practice at the Hospital - Aslamiyah, Suwai Batul; Basit, Mohammad; Wijaksono, M. Arief; Fetriyah, Umi Hanik (Indonesian Journal of Global Health Research, 2024)
Nursing students engage in clinical practice to apply nursing theory, integrate theoretical knowledge and practical skills. Effective clinical supervision allows students to experience satisfaction during clinical practice and meet cognitive, psychomotor, and affective competencies. It is important to research studying clinical supervision and student satisfaction in the Nursing DIII program during clinical practice at Hospital, so the objective this research is to determine the relationship between clinical guidance and the satisfaction of DIII Nursing students during clinical practice at Hospital. Methods: this study is descriptive with quantitative design with cross sectional. Sampling using continous sampling and sample used was 75 students of DIII regular nursing XXV. Data collection using questionnaires that tested valid and reliability. Analysis of data using Fisher Exact Test. Results: most of the clinical guidance is good majority (69.3%) and on the satisfaction of respondents when the majority clinical practice is satisfied (89.3%). The relationship of clinical guidance with nursing student satisfaction during clinical practice at the hospital with the results of p value 0.016 with (α = 0.05). Conclusion: there is a relationship of clinical guidance with nursing student satisfaction during clinical practice at the hospital. it is expected that the clinical supervisor to increase empathy by conducting clinical guidance to students in order to have a positive impact on students.